Anti-Ro52 antibodies in idiopathic inflammatory myopathies: clinical significance across myositis-specific antibody-defined subgroups - Qi Pan; Shuai Li; Xinyue Guo; Shanshan Li; Yiran Chen; Huihui Ji; Xiaoqin Luo; Yunfeng Dai; Longyang Zhu; Chen Zong; Lin Luo; Ying Li; et al. (Rheumatology, 2026)
Abstract Objective To investigate the frequency, clinical characteristics, and prognostic value of anti-Ro52 antibodies in patients with idiopathic inflammatory myopathies (IIMs), especially in IIM subgroups with distinct myositis-specific antibodies (MSAs). Methods This cohort included 2,126 patients with IIMs treated at the China-Japan Friendship Hospital between April 2002 and April 2023. Associations between clinical features and outcomes with anti-Ro52 antibodies were evaluated in each MSA-defined subgroup. Results In total, 978 (46.0%) patients presented with anti-Ro52 antibody positivity. Anti-Ro52 antibodies represented the most common myositis-associated antibody in IIM patients, with notably higher frequencies observed in patients with anti-MDA5+ dermatomyositis (DM) and anti-synthetase syndrome (ASyS) compared to other IIM serotypes. In patients with anti-MDA5+ DM, anti-Ro52 antibodies were associated with interstitial lung disease (ILD), rapidly progressive ILD, and worse prognosis. Coexistence of anti-Ro52 and anti-SSA antibodies was further associated with a worse prognosis in anti-MDA5+ DM. In ASyS, anti-Ro52 antibodies were associated with pulmonary involvement but not with prognosis. In other MSA-defined subgroups, the clinical significance of anti-Ro52 antibodies was limited. Conclusion Anti-Ro52 antibodies are highly prevalent in patients with IIMs, especially those with anti-MDA5+ DM and ASyS. Anti-Ro52 antibody testing may be a valuable tool for risk stratification and prognostic assessment in anti-MDA5+ DM and ASyS.